The solitary wave solutions to the fractional Radhakrishnan-Kundu-Lakshmanan model - Sulaiman, Tukur Abdulkadir; Bulut, Hasan (World Scientific Publ Co Pte Ltd, 2019)
This study addresses the local M-fractional Radhakrishnan-Kundu-Lakshmanan (RKL) equation by utilizing the extended rational sine-cosine/sinh-cosh methods. We give the constraint conditions which guarantee the existence of the valid solitons and other solutions to the studied model. The reported solutions may be useful in explaining the physical meaning of the RKL equation and some other related nonlinear phenomena arising in nonlinear sciences.
Keywords: Local M-fractional derivative; optical soliton